2018
DOI: 10.3390/ijms19123820
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-Dependent Changes of Protein Palmitoylation: Impact on Nuclear Enzymes and Regulation of Gene Expression

Abstract: Diet is the main environmental stimulus chronically impinging on the organism throughout the entire life. Nutrients impact cells via a plethora of mechanisms including the regulation of both protein post-translational modifications and gene expression. Palmitoylation is the most-studied protein lipidation, which consists of the attachment of a molecule of palmitic acid to residues of proteins. S-palmitoylation is a reversible cysteine modification finely regulated by palmitoyl-transferases and acyl-thioesteras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 147 publications
(172 reference statements)
0
28
0
Order By: Relevance
“…In cells, palmitoylation of viral membrane proteins facilitate membrane fusion by SARS-CoV and some IAV strains [ 34 , 35 ]. Although the mechanism has not been elucidated, an increase of palmitoylation of some proteins in obese mice suggests an alteration in this pathway [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cells, palmitoylation of viral membrane proteins facilitate membrane fusion by SARS-CoV and some IAV strains [ 34 , 35 ]. Although the mechanism has not been elucidated, an increase of palmitoylation of some proteins in obese mice suggests an alteration in this pathway [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study also showed that overexpression of a non-acylated CD36 mutant in the liver of mice protected against NASH development, implicating CD36 S-acylation in the pathogenesis of this disease. In this regard, dietary lipids, insulin signaling, and ethanol metabolism can alter the palmitoylome (57)(58)(59)(60). For instance, feeding of a high-fat diet (~60% calories from saturated FAs) was associated with hyper-palmitoylation and dysregulation of AMPA glutamate receptor subunit GluA1 in the brain (60).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the palmitoylation of proteins involved in fat and carbohydrate transport and signalling may compromise digestion. Articles reviewing the biological effects of protein palmitoylation have anticipated a functional role in lipid and glucose metabolism 49 , 50 , though ZDHHC6 is not currently implicated. ZDHHC6 localises in the endoplasmic reticulum and is reported to be involved in the palmitoylation of five protein targets 51 – 56 .…”
Section: Discussionmentioning
confidence: 99%